ISLAMIC MORALS AS A BASIS FOR COMMUNICATION ETHICS ON SOCIAL MEDIA AMONG MUSLIM TEENAGERS - Syaqira Assyabirra; Suci Mulia (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2025)
The rapid development of information technology has transformed the communication patterns of Muslim youth, particularly through social media, which has now become a primary platform for interaction. While it offers many benefits, social media also presents serious challenges, such as the rise of hate speech, the spread of misinformation, and the use of impolite language. These phenomena indicate a decline in moral and ethical values in digital communication, highlighting the need to instill the principles of Islamic morals (akhlaq Islami) as a foundation for healthy communication ethics. The problem formulation in this study is how the concept of Islamic morals can serve as a guideline in shaping the communication behavior of Muslim youth on social media. The research questions are: which principles of Islamic morals are relevant to online interactions, and how their application can foster polite and ethical communication. This study employs a library research method by reviewing literature sources from books, scholarly journals, articles, and relevant documents discussing Islamic morals, communication ethics, and youth behavior on social media. The findings reveal that values such as sidq (truthfulness), hifz al-lisan (guarding speech), amanah (trustworthiness), ta’awun (mutual help), and iffah (chastity) are highly relevant in shaping positive digital communication ethics. Applying these values can enhance ethical awareness among Muslim youth, promote polite behavior, reduce the spread of negative content, and foster constructive interaction in digital spaces. This study emphasizes the importance of the role of education, family, and community in internalizing Islamic moral values through Islamic-based digital literacy training so that Muslim youth can become responsible, polite, and beneficial social media users for society